Electron spin flip Raman spectroscopy of the diluted magnetic semiconductor Zn1‐xMnxSe below the metal‐insulator transition. Issue 7 (9th February 2016) - Knapp, A. G.; Petznick, S.; Jansson, F.; Wiemer, M.; Hetterich, M.; Gebhard, F.; Baranovskii, S. D.; Klar, P. J.; Geurts, J.
Abstract: In n‐doped (Zn, Mn)Se, the (s, d) exchange influences the ground state level of the donor‐bound electrons in an external B‐field, depending on their local Mn environment. Due to the statistical Mn arrangement, this should induce a broadening of the donor energy distribution, inducing a magneto‐resistance in transport, and also a broadening of the energy distribution of donor‐bound excitons ( D 0, X ). We have investigated this broadening for Zn0.94 Mn0.06 Se:Cl (n= 4.5×10 17 cm ‐3 ) by electronic spin flip Raman spectroscopy (ESFRS) on the donor electrons. Utilizing the resonant enhancement of the ESFRS intensity upon resonance of the laser light with ( D 0, X ), we actually observe a significant broadening of the ESFRS resonance profiles with increasing B‐field, up to 11.5 meV (FWHM) for B = 5 T. Furthermore we detect a second resonance profile contribution, whose FWHM shows a much weaker B‐field dependence. We assign this contribution to a resonance mediated by the free‐exciton ( X 0 ). Our Raman results agree very well with magneto‐transport results at the same sample. (© 2016 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)